Solomon Islands : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This Selected Issues paper examines prospects for increasing growth and reducing poverty in the Solomon Islands. The paper highlights that agriculture constitutes the largest sector of the Solomon Islands economy, averaging about 20 percent of GDP throughout the 1990s. The Solomon Islands also has large fish resources, and the fisheries sector accounted for an average of 7 percent of GDP and 30 percent of total exports in the 1990s. The paper also examines the state of the financial sector in the Solomon Islands.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet